Turbulent forced convection in a helically coiled square duct with one uniform temperature and three adiabatic walls - Kaya, O; Teke, I (SPRINGER, 2005)
In this study, effects of geometrical parameters on the average convection heat transfer characteristics in helical square ducts were investigated both experimentally and numerically. The inner wall of the helical square duct was uniformly temperatured, and the top, bottom, and outer walls were adiabatic. The Renormalization Group (RNG) k-epsilon turbulence model was used to simulate turbulent flow and heat transfer. The governing equations were solved by a finite volume method. Numerical results were found to be in good agreement with the presented experimental data. The new correlation was proposed for the average heat transfer coefficient on the inner wall of the helical square duct. The results showed that the ratio of pitch to coil radius b/R has no obvious effect on the inner wall convective heat transfer coefficient but the ratio of hydraulic radius to coil radius a/R has considerable effect.
Keywords: HEAT-TRANSFER; LAMINAR-FLOW; RECTANGULAR DUCTS; ENTRANCE REGION; CURVED PIPE; PITCH; Thermodynamics; Mechanics